Analysis of the lasing characteristics of InGaAs/GaAs WGM microlasers. (December 2020) - Kryzhanovskaya, N V; Moiseev, E I; Zhukov, A E; Zubov, F I; Kalyuzhnyy, N A; Mintairov, S A; Guseva, Yu A; Tikhomirov, V G; Kulagina, M M; Kadinskaya, S A; Vinogradov, A Yu; Maximov, M V
Abstract: We present an analysis of spectral and threshold characteristics of InGaAs/GaAs quantum well-dot microdisk laser operated under cw current injection at room temperature without external cooling. The experimental values of the threshold current for the disk and ring microlasers are compared. We observe that the threshold current can be significantly decreased in devices with large diameters (more than 30 μm) by using the ring geometry.